Desenvolvimento regional e mercado de trabalho formal: uma análise para o Maranhão e suas regiões geográficas no período de 2000 a 2016 - SILVA, Rafael Thalysson Costa (2019)
The main objective of this dissertation is to present and analyze the evolution of formal employment in Maranhão and its geographical regions, from 2000 to 2016, with the main intention of understanding possible changes in its productive structure. The research procedure adopted consists of bibliographical research and the analysis of formal employment through data from the Annual Social Information Relation (RAIS). To understand and deepen this study, it was important to briefly present regional economic development theories, to understand the behavior of the Brazilian labor market in the chosen period, and also to try to understand the regional economic reality of the state of Maranhão. In the period studied there was a quantitative increase in formal employment in all the regions of Maranhão, but in a qualitative perspective, which analyzes the sectoral diversification of the productive activity of the region, it is verified that the growth of formal employment happened concentrated in few sectors of the economy of the regions, aimed at low wages, and therefore, there are no changes in the existing productive structure, which characterizes its underdeveloped condition.